2009
DOI: 10.1038/gene.2009.101
|View full text |Cite
|
Sign up to set email alerts
|

HLA-class I markers and multiple sclerosis susceptibility in the Italian population

Abstract: Previous studies reported an association with multiple sclerosis (MS) of distinct HLA-class I markers, namely HLA-A*02, HLA-Cw*05 and MOG-142L. In this work, we tested the association with MS of A*02 and Cw*05 in 1273 Italian MS patients and 1075 matched controls, which were previously analyzed for MOG-142, and explored the relationship among these three markers in modulating MS risk. HLA-A*02 conferred a statistically robust MS protection (odds ratio, OR ¼ 0.61; 95% confidence intervals, CI ¼ 0.51-0.72, Po10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 27 publications
7
35
0
Order By: Relevance
“…This opposite behavior has been observed for other HLA alleles, for example, associated with MS susceptibility and belonging to different ancestral HLA haplotypes. 24 It is worth noting that HLA A*32 and DRB1*1501 are part of the HLA-A19 haplotype (with the closely linked alleles HLA A*29, A*30 and A*33) that was found significantly under-transmitted in MS patients. 25 Although with caution owing to the exploratory nature of our analysis and without the support of functional studies, we hypothesized that the observed HLA DRB1*1501 modulation of the effect of several HLA alleles might suggest epistatic models of allele interactions.…”
Section: Hla Alleles and Mri In Ms M Liguori Et Almentioning
confidence: 99%
“…This opposite behavior has been observed for other HLA alleles, for example, associated with MS susceptibility and belonging to different ancestral HLA haplotypes. 24 It is worth noting that HLA A*32 and DRB1*1501 are part of the HLA-A19 haplotype (with the closely linked alleles HLA A*29, A*30 and A*33) that was found significantly under-transmitted in MS patients. 25 Although with caution owing to the exploratory nature of our analysis and without the support of functional studies, we hypothesized that the observed HLA DRB1*1501 modulation of the effect of several HLA alleles might suggest epistatic models of allele interactions.…”
Section: Hla Alleles and Mri In Ms M Liguori Et Almentioning
confidence: 99%
“…Recently, particular attention has been on the protective effects of some of the class I HLA molecules. HLA-A*02 has been reported to confer protection against MS in multiple casecontrol studies (Bettencourt et al 2012;Bergamaschi et al 2010Bergamaschi et al , 2011Brynedal et al 2007;Burfoot et al 2008;Link et al 2010;Rubio et al 2002;Sawcer et al 2011;Silva et al 2009). However, a protective effect of HLA-A*02 was not observed in studies investigating transmission of HLA in MS families (Chao et al 2007), and recent reports suggest that HLA-A*02 might only exert protective effects in the absence of HLA-DRB1*15:01 (Link et al 2012).…”
Section: Hla Moleculesmentioning
confidence: 96%
“…Genetic susceptibility to MS is mainly located within the MHC region (Ascherio and Munger 2007a;Brynedal et al 2007;Gale and Martyn 1995;Lincoln et al 2005), but several other non-MHC genetic loci have been observed to confer a less pronounced influence on MS risk (Bergamaschi et al 2010;Burfoot et al 2008).…”
Section: Gene-environment Interactionsmentioning
confidence: 99%
“…As in most autoimmune/inflammatory disorders, the strongest genetic associations with MS are located within the human leukocyte antigen (HLA) complex. The class II allele HLA-DRB1*15 increases the risk of developing MS in almost all populations, with an odds ratio (OR) around 3 (Lincoln et al 2005), whereas the class I allele HLA-A*02 has a protective effect with an OR of approximately 0.7 (Bergamaschi et al 2010;Brynedal et al 2007;Burfoot et al 2008). Over recent years, genome-wide association studies (GWAS) have identified a large number of genetic regions outside the HLA complex that influence disease susceptibility.…”
Section: Introductionmentioning
confidence: 99%